Penerapan Arsitektur Ekologi Dalam Perencanaan dan Perancangan Fasilitas Pengolahan Sampah Terpadu di Kabupaten Tabanan, Provinsi Bali: Bahasa Indonesia - I Putu Yuda Ari Putra Vinantha; Kadek Tania Utami Putri; Anak Agung Bagus Bayu Anggawirya; I Kadek Merta Wijaya (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2026)
Waste management remains a major environmental issue in Indonesia, as indicated by the high proportion of unmanaged waste, particularly in Bali Province and Tabanan Regency. Based on SIPSN data in 2024, Tabanan Regency shows a relatively high percentage of unmanaged waste compared to other Sarbagita regions, while limited availability and distribution of TPS3R facilities have hindered optimal waste management. This study aims to plan and design an Integrated Waste Processing Facility in Tabanan Regency that functions not only as a waste treatment center but also as an environmental education facility. The research method includes secondary data collection through literature review and SIPSN data, as well as primary data obtained from field observations and interviews with TPS3R managers, followed by quantitative and qualitative analysis. The results propose a design concept based on ecological architecture and the 3R principles (Reduce, Reuse, Recycle), emphasizing efficient mass arrangement, the use of environmentally friendly materials, natural lighting and ventilation, and the provision of public and educational spaces to support sustainable waste management in Tabanan Regency.